Test-beam and simulation studies towards RPWELL-based DHCAL. (1st December 2022) - Shaked-Renous, D.; Amaro, F.D.; Bhattacharya, P.; Breskin, A.; Chefdeville, M.; Drancourt, C.; Geralis, T.; Karyotakis, Y.; Moleri, L.; Tesi, A.; Titov, M.; Veloso, J.; et al.
Abstract: Digital Hadronic Calorimeters (DHCAL) were suggested for future Colliders as part of the particle-flow concept. Though studied mainly with RPC, studies focusing on sampling elements based on Micro-Pattern Gaseous Detector have shown the potential advantages; they can be operated with environment-friendly gases and reach similar detection efficiency at lower average pad multiplicity. We summarize here the experimental test-beam results of a small-size DHCAL prototype, incorporating six Micromegas and two RPWELL sampling elements, interlaced with steel-absorber plates. It was investigated with 2–6 GeV pion beams at the CERN/PS beam facility. The data permitted validating a GEANT4 simulation framework of a DHCAL, and evaluating the expected pion energy resolution of a full-scale RPWELL-based calorimeter. The pion energy resolution derived for the RPWELL concept is competitive to that of glass RPC and Micromegas sampling techniques.